Pengaruh Perencanaan Pajak, Aset Pajak Tangguhan dan Beban Pajak Tangguhan terhadap Manajemen Laba - Handayani, Mery; Utami, Tri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to analyze and test the influence of tax planning, deferred tax assets and deferred tax expenses on earnings management. The population in this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The method used in this research is a descriptive research method with a quantitative approach using secondary data, namely in the form of financial reports and annual reports. The sampling technique in this research is purposive sampling. Based on predetermined criteria, a total of 26 Consumer Non-Cyclicals companies were listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The analysis techniques used in this research are descriptive analysis, panel data regression model testing, classical assumption testing, multiple linear regression testing and hypothesis testing. The results of this research show that deferred tax planning and deferred tax expenses have no effect on earnings management. Meanwhile, deferred tax assets have an effect on earnings management. Then, simultaneous research on tax planning, deferred tax assets and deferred tax expenses influences earnings management.